GEODESICHESKOE OBESPECHENIE STROITELSTVA MOSTOV AND MOSTOVYKH PEREKHODOV - Kunslyamov K.B., Кунслямов К.Б. (Рroblems of engineering and professional education, 2023)
In this article, the main geodetic works that ensure the construction of the bridge It is taken into account when providing the state and quantity of the building and its individual parts. separating work and its precise execution are described.